Specific features of 3, 6-bis (4-hydroxy phenyl)-piperazine-2, 5-dione (BHPPD) diphenolic monomer and compered with toxic industrial bisphenol-A (BPA): DFT calculation - Moghadam, Ghasem; Tirgir, Farhang; Reshak, Ali H.; Khorshidi, Mahsa (Elsevier, 2019)
In this study calculations of IR spectra, Mullikan charge analysis, molecular structures, energy optimization, molecular masses, dipole moments, polarizations, atomic electronic charges, HOMO and LUMO energies, gap energies, hardness, softness, electron affinities, chemical potentials and investigate of electro static potentials have been performed. The density functional theory (DFT) within the B3LYP method and 6-31G/6-311G* basis sets on BPA and BHPPD were used. A comprehensive comparison between the two methods was presented. The computations demonstrate that the 3, 6-bis (4-hydroxy phenyl)- piperazine-2, 5-dione (BHPPD) monomer can be viewed as another biodegradable diol which might be utilized as substitutes for the mechanically utilized poisonous diphenols, for example, bisphenol-A (BPA). BHPPD can be utilized as a part of the outline of biodegradable materials as grocery contact surface veneer coatings for jars, metal containers capping, defensive veneers and completions, vehicle parts, glues, aviation applications and as a covering for PVC tubes. The examination amongst BPA and BHPPD demonstrated that the novel nonpoisonous integrated fragrant diol has better physicochemical and poisonous properties contrasted with that of BPA. © 2019 Elsevier B.V.